Teori Humanistik Abraham Maslow dalam Meningkatkan Motivasi Belajar Peserta Didik pada Pembelajaran Fikih - Ruhaya, Besse; Muhaimin, Muhammad; Qadri, Muhammad; Darussalam, Andi Baso (Faculty of Tarbiyah and Teacher Training, 2026)
Low student motivation in Fiqh subjects is often caused by rigid learning processes that overlook psychological aspects and individual needs. This study aims to describe the application of Abraham Maslow’s humanistic learning theory in increasing student motivation in Fiqh learning at MA Syekh Yusuf Sungguminasa. The research utilizes a descriptive qualitative method, with data collected through observation and in-depth interviews. The results indicate that the humanistic approach significantly impacts the improvement of student motivation through the systematic fulfillment of the hierarchy of needs. By meeting basic needs up to esteem, students are able to reach the stage of self-actualization within the learning process. The implications of this study emphasize that Fiqh educators need to integrate humanistic approaches to create a more meaningful and humane learning environment, ultimately fostering the optimal development of student potential.